Cognitive Mechanisms of Monolingual and Bilingual Children in Monoliterate Educational Settings: Evidence From Sentence Repetition - Andreou, Maria; Tsimpli, Ianthi Maria; Masoura, Elvira; Agathopoulou, Eleni (Frontiers in Psychology, 2021)
Sentence Repetition (SR) tasks have been extensively employed to assess bilingual children’s linguistic and cognitive resources. The present study examined whether monoliterate bilingual children differ from their monolingual (and monoliterate) peers in SR accuracy and cognitive tasks, and investigated links between vocabulary, updating, verbal and visuospatial working memory and SR performance in the same children. Participants were two groups of 35 children, 8 to 12 years of age: one group consisted of Albanian-Greek monoliterate bilingual children and the other of Greek monolingual children attending a monolingual-Greek educational setting. The findings demonstrate that the two groups performed similarly in the grammaticality scores of the SR. However, monolinguals outperformed the monoliterate bilinguals in SR accuracy, as well as in the visuospatial working memory and updating tasks. The findings did not indicate any bilingual advantage in cognitive performance. The results also demonstrate that updating and visuospatial working memory significantly predicted monolingual children’s SR accuracy scores, whereas Greek vocabulary predicted the performance of our monoliterate bilingual children in the same task. We attribute this outcome to the fact that monoliterate bilingual children do not rely on their fluid cognitive resources to perform the task, but instead rely on language proficiency (indicated by expressive vocabulary) while performing the SR.